Preparation method of a viscosity sustained-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide emulsion and dry powder
By introducing temperature-resistant and salt-resistant monomers into the polymer and forming shell polymer particles, the problem of poor viscosity stability of polymer under high temperature and high mineralization is solved, and the efficient slow-release viscosity release of polymer is achieved, which extends the polymer The service life is improved and the oil displacement efficiency is improved.
Patent Information
- Application Number
- CN202410584983.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-05-13
AI Technical Summary
The existing polymer oil flooding technology is difficult to maintain high viscosity stability under high temperature and high mineralization conditions, resulting in low recovery and serious viscosity loss of polymers in the formation, affecting the oil flooding effect.
The preparation method of viscosity sustained release high temperature-resistant, salt-resistant, oil-repellent-repellent polyacrylamide emulsion and dry powder is adopted. Through reverse phase emulsion polymerization and suspension polymerization technology, ultra-high molecular weight polymer particles with shells are formed, and the shells are slow at high temperatures. Water releases polymers, extends service life and maintains high viscosity.
It significantly improves the viscosity stability and action time of the polymer, reduces the viscosity loss in the initial stage of injection, improves the oil displacement efficiency, and maintains efficient oil displacement performance under high temperature and high mineralization conditions.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of water-soluble polymers, and more specifically, relates to a viscosity slow-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide, and a preparation method of the viscosity slow-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide emulsion and dry powder. Background Art
[0002] As the most important technology for tertiary oil recovery, polymer flooding technology greatly improves the oil-water mobility ratio during oil recovery by increasing the viscosity of the water phase, thereby slowing down the rate of increase of water content in the produced fluid, making the actual oil recovery efficiency closer to the limit oil recovery efficiency, or even reaching the limit oil recovery efficiency. It is an important technical means to improve the recovery rate of old oil fields. Among the 2.5 billion tons of crude oil recovered from old oil fields, 300 million tons come from polymer flooding. According to statistics, the average production-injection ratio of polymer flooding is more than 30:1, and the injection-production ratio of high-performance oil recovery polymers even reaches 60:1.
[0003] The solubility of polymer molecules and the viscosity and stability in aqueous solution after dissolution are the key factors that determine the effect of enhanced oil recovery. The initial solution viscosity of polymer is a very important factor. To improve the performance of polymer, the most important thing is to increase the initial solution viscosity of polymer, and the most direct and effective way is to increase the molecular weight of polymer. Therefore, increasing the molecular weight is the first choice to increase the initial viscosity of polymer. The increase of polymer molecular weight directly increases the hydrodynamic volume of polymer molecules, reduces the critical overlap concentration of polymer molecules, and increases the apparent viscosity of its solution. However, if the composition and structure of polymer molecules are not changed, simply increasing the molecular weight of polymer can only increase the initial viscosity of polymer in clear water at room temperature. Under high temperature and high mineralization conditions, the stability still decreases significantly; the second method to increase the initial viscosity of polymer is hydrophobic associating flooding polymer. Introducing water-insoluble hydrophobic groups into polymer monomers makes polymers amphiphilic. Due to the obvious van der Waals force between hydrophobic groups, various phase separation microstructures of different sizes are formed, so that the polymer solution becomes a bulk dispersion system connected to each other through these microstructures. Compared with water-soluble polymers in solution state, under the same apparent viscosity measurement method, a larger initial viscosity value is obtained. However, the introduction of hydrophobic monomers does not improve the viscosity stability of the polymer solution. Since the polymer itself has a low molecular weight, when the polymer enters the formation, it is affected by formation adsorption and high temperature and high mineralization, resulting in a large loss of viscosity.
[0004] In order to improve the stability of the polymer, some researchers have proposed another type of slow-release viscosity-enhancing polymer. A breakable cross-linking agent is used in the polymer to cross-link the polymer. As the cross-linking points break, the polymer slowly releases viscosity. For example, in Chinese invention patent 202111567597.4, acrylic esters of diols, triols, and tetraols are used as cross-linking agents to synthesize a type of slow-release viscosity-enhancing polymer microsphere. After this polymer is added to water, the polymer changes from a bulk type to a linear type as the ester hydrolyzes, releasing viscosity. However, as the ester bond of this polymer hydrolyzes, the amide group of the polymer is also hydrolyzed. When the ester bond is completely broken, the polymer changes from a bulk type to a linear type. However, due to the increase in the degree of hydrolysis of the polymer itself, the viscosity released under high temperature and high mineralization conditions is also difficult to meet the use requirements of high temperature and high mineralization reservoirs.
[0005] High-performance oil recovery polymers must have a high solution viscosity, but high viscosity cannot only focus on the initial viscosity of the polymer solution, but should emphasize the viscosity that can be maintained for a long time after entering the formation. Only high viscosity maintained deep in the formation can effectively change the oil-water mobility ratio inside the reservoir, increase the diversion coefficient of the oil phase, and improve the recovery rate. At present, the most important indicator of all oil recovery polymer standards is still the initial viscosity of the polymer solution, while the viscosity stability of the polymer is not required to be high, which is why many polymers with high initial viscosity do not have a good oil recovery effect. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a viscosity slow-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide emulsion and dry powder particles; the structure of the present invention can greatly avoid the shearing of ultra-high molecular weight and high-viscosity polymer solutions when passing through blastholes and near-well areas, reduce the viscosity loss in the initial injection stage, and at the same time improve the polymer viscosity stability and action time.
[0007] The technical solution provided by the present invention is:
[0008] A method for preparing a viscosity slow-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide emulsion: This method is obtained by oil-in-water, i.e., reverse emulsion polymerization, including the polymerization process of the reverse emulsion, the preparation polymerization of the shell layer, and the phase inversion treatment process of the emulsion after polymerization.
[0009] The reverse phase emulsion comprises 10-40wt% of an organic solvent, 0.5-20wt% of a surfactant added before polymerization, 0.5-10wt% of a surfactant for phase inversion, 5-50wt% of water, 10-45wt% of a monomer, a base to make the final pH of the system between 6 and 8, and an initiator accounting for 0.001-1wt% of the total monomer amount; wherein the monomer comprises a nonionic monomer and an anionic monomer, the amount of the nonionic monomer accounts for 30-95wt% of the total monomer amount, and the anionic monomer accounts for 5-70wt% of the total monomer amount; wherein the initiator is a redox initiator or a mixture of a redox initiator and a water-soluble azo initiator in any mass ratio; and the above amounts are calculated in mass percentage.
[0010] The organic solvent is one of toluene, xylene, normal alkane, isoalkane, petroleum ether, liquid paraffin, white oil, kerosene and diesel oil, or a mixture of two or more of them in any mass ratio. The amount of the organic solvent used is 10-40wt% relative to the final product. The surfactant includes a surfactant for emulsification added before polymerization and a surfactant for diversion added after polymerization, a single surfactant or a mixture of two or more surfactants in any mass ratio, the final HLB value of the added surfactant or surfactant mixture is between 3-8, and the surfactant for emulsification added before polymerization is one of glyceryl monostearate, sorbitan monooleate, sorbitan monostearate, sorbitan monopalmitate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether and polyoxyethylene sorbitan monostearate, or a mixture of two or more of them in any mass ratio. The amount of the surfactant added before polymerization relative to the final product is 0.5-20wt%, the HLB value of the surfactant added after polymerization for phase inversion is greater than 8, the surfactant added after polymerization for phase inversion is one of nonionic surfactants or anionic surfactants or a mixture of two or more in any mass ratio, the nonionic surfactant is fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, alkylphenol polyoxyethylene ether, fatty amine polyoxyethylene ether or alkyl alcohol amide polyoxyethylene ether. The anionic surfactant is sodium dodecylbenzene sulfonate or sodium sulfate of fatty alcohol polyoxyethylene ether. The amount of the surfactant for phase inversion relative to the final product is 0.5-10wt%. The water is deionized water, distilled water or pure water, and its amount relative to the final product is 5-50wt%. The monomers include nonionic monomers and anionic monomers, and the nonionic monomers are one of acrylamide, 2-methylacrylamide, N-tert-butylacrylamide, N,N-dimethylacrylamide, N-vinylpyrrolidone or a mixture of two or more in any mass ratio. The anionic monomer is one of acrylic acid, methacrylic acid, itaconic acid, maleic acid, 2-acrylamide-2-methylpropanesulfonic acid, methylallylsulfonic acid, and vinylbenzenesulfonic acid, or a mixture of two or more in any mass ratio. The amount of the monomer relative to the final product is 10-45wt%, wherein the amount of acrylamide nonionic monomer accounts for 30-95wt% of the total monomer amount, and the amount of the anionic monomer accounts for 5-70wt% of the total monomer amount. The alkali is sodium hydroxide, potassium hydroxide, sodium carbonate or ammonia water, and the amount of the alkali added matches the amount of the anionic monomer added, so that the final pH of the system is between 6 and 8. The initiator is a redox initiator or a composite initiator of a redox initiator and a water-soluble azo initiator in any mass ratio. The oxidant in the redox initiator is ammonium persulfate, sodium persulfate or potassium persulfate, and the oxidant in the reduction initiator is hydrogen peroxide and organic hydroperoxides, such as tert-butyl hydroperoxide or isopropylbenzene hydroperoxide.The reducing agent in the redox initiator is a sulfite such as sodium sulfite, sodium bisulfite, sodium pyrosulfite, ferrous sulfate, tetramethylethylenediamine or β-dimethylaminopropionitrile, the water-soluble azo is azobisisobutylamine hydrochloride, azobispropaneamine or azobiscyanovaleric acid, and the amount of the initiator used accounts for 0.001-1wt% of the total monomer amount.
[0011] The polymerization process of the reverse emulsion includes: (1) preparation of the organic phase, adding a certain amount of organic solvent to a polymerization kettle equipped with a stirring device, and then continuing to add a certain amount of surfactant or a mixture of surfactants to the polymerization kettle, stirring and mixing uniformly; (2) preparation of the aqueous phase, adding a certain amount of water to another liquid preparation kettle equipped with a stirring device, and then adding a certain amount of monomers in sequence, adding alkali to adjust the pH value of the system, cooling, and adding initiator; (3) mixing and emulsification, introducing the prepared aqueous phase into the polymerization kettle containing the organic phase, stirring and mixing, and further emulsifying by an emulsification pump at the bottom of the kettle to obtain a more stable emulsion; (4) polymerization, introducing an inert gas into the polymerization kettle, and at the same time controlling the starting temperature of the system at 8-25°C to carry out a polymerization reaction, and controlling the polymerization reaction time by the amount of initiator added. As the polymerization reaction proceeds, the system temperature slowly rises, and the maximum temperature reaches 50-75°C.
[0012] The shell layer preparation polymerization process is as follows: monoacrylate and diacrylate of polyethylene glycol (PEG) are added to the polymerized emulsion. According to the principle of similar compatibility, acrylate will penetrate the surfactant layer and enter between the water phase and the surfactant, wherein the PEG chain faces the water phase, and the acrylate chain is compatible with the surfactant, so that a shell layer composed of acrylate of polyethylene glycol and surfactant is formed on the surface of the polymer particles. At this time, an initiator is added to initiate the polymerization of acrylate, and the monoacrylate and diacrylate of polyethylene glycol (PEG) will be fixed on the polymer surface to form a shell layer. The specific process is to keep the system temperature at 40-65°C after the polymerization process is completed, add an appropriate amount of monoacrylate and diacrylate of polyethylene glycol (PEG) to the system, stir for 10-60 minutes, and add an appropriate amount of initiator to initiate the polymerization of the shell layer. The amount of monoacrylate and diacrylate of polyethylene glycol (PEG) added is 0.5-2wt% of the total amount of the emulsion, wherein the mass ratio of diacrylate of polyethylene glycol (PEG) to monoacrylate of polyethylene glycol (PEG) is 3:1-5:1. The degree of polymerization of PEG is 100, 200, 400 or 600. The initiator is azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
[0013] The phase inversion process is as follows: after the shell layer preparation polymerization reaction is completed, the system is cooled to below 30°C, the required surfactant for phase inversion is added to the polymerization kettle, stirred for 30-60 minutes, the emulsion is subjected to phase inversion treatment, and the finished product is obtained after phase inversion.
[0014] A method for preparing a viscosity slow-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide dry powder is obtained by suspension polymerization, including a suspension polymerization polymerization process, a shell layer preparation polymerization process, and a suspension particle separation and drying process.
[0015] The suspension of suspension polymerization comprises 40-90wt% of organic solvent, 0.1-2wt% of suspending agent, water, 10-45wt% of monomer, alkali to make the final pH of the system between 6-8 and 0.001-1wt% of initiator based on the total amount of monomer, wherein the amount of water accounts for 50-80wt% of the total amount of water and monomer; the monomer comprises nonionic monomer and anionic monomer, wherein the amount of nonionic monomer accounts for 30-95wt% of the total amount of monomer, and the amount of anionic monomer accounts for 5-70wt% of the total amount of monomer; the initiator is a redox initiator or a composite initiator of a redox initiator and a water-soluble azo initiator; the above amounts are calculated by mass percentage.
[0016] The organic solvent is any one or more organic solvents known to those skilled in the art, such as toluene, xylene, normal alkane, isoalkane, petroleum ether, liquid paraffin, white oil, kerosene, diesel oil, or any mixture of any mass ratio of two or more thereof. The amount of organic solvent used is 40-90wt% relative to the final product. The suspending agent is not particularly limited, and is a surfactant or polymer known to those skilled in the art, such as sorbitan monopalmitate, sorbitan monostearate, sorbitan tristearate, sorbitan monooleate, and polymers such as polymethacrylate dodecyl, ethyl cellulose, and the amount of suspending agent added is 0.1-2wt% relative to the amount of the final product. The amount of suspending agent added, the ratio of oil phase to water phase, and the stirring speed are adjusted to control the particle size of the water phase so that the particle size is within the range of 0.5-2 mm. The water is deionized water, distilled water, or pure water, and the amount of water used accounts for 50-80wt% of the total amount of water and monomer.
[0017] The monomers include nonionic monomers and anionic monomers, wherein the nonionic monomers are acrylamide, 2-methylacrylamide, N-tert-butylacrylamide, N,N-dimethylacrylamide, and N-vinylpyrrolidone, or a mixture of two or more of them in any mass ratio, and the anionic monomers are acrylic acid, methacrylic acid, itaconic acid, maleic acid, 2-acrylamide-2-methylpropanesulfonic acid, methylallylsulfonic acid, and vinylbenzenesulfonic acid, or a mixture of one or more of them in any mass ratio. The amount of the monomers used relative to the final product is 10-45wt%, wherein the amount of acrylamide nonionic monomers accounts for 30-95wt% of the total amount of monomers, and the amount of anionic monomers accounts for 5-70wt% of the total amount of monomers. The base is not particularly limited, as long as it can play a role in neutralizing anionic monomers, such as sodium hydroxide, potassium hydroxide or sodium carbonate, and the amount of the base added matches the amount of the anionic monomers added, so that the final pH of the system is between 6 and 8.
[0018] The initiator is a redox initiator or a composite initiator of a redox initiator and a water-soluble azo initiator in any mass ratio. The oxidant in the redox initiator is a persulfate, such as ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide; organic hydrogen peroxide, such as tert-butyl hydroperoxide, isopropylbenzene hydroperoxide; the reducing agent in the redox initiator is a sulfite, such as sodium sulfite, sodium bisulfite, sodium pyrosulfite, ferrous sulfate, tetramethylethylenediamine, β-dimethylaminopropionitrile. The water-soluble azo is such as azobisisobutylamine hydrochloride, azobispropaneamine, azobiscyanovaleric acid. The amount of the initiator is 0.001-1wt% of the total monomer amount.
[0019] The polymerization process of the suspension polymerization includes: 1. preparation of the organic phase, adding a certain amount of organic solvent into a polymerization kettle equipped with a stirring device, and then continuing to add a certain amount of suspending agent into the polymerization kettle, stirring and mixing uniformly; 2. preparation of the aqueous phase, adding a certain amount of water into another liquid preparation kettle equipped with a stirring device, and then adding a certain amount of monomers in sequence, adding alkali to adjust the pH value of the system, cooling, and adding initiator; 3. mixing and stirring, introducing the prepared aqueous phase into the polymerization kettle containing the organic phase and stirring and mixing, and controlling the stirring speed so that the size of the suspended particles is 0.5-2mm; 4. polymerization, introducing an inert gas into the polymerization kettle, and at the same time controlling the starting temperature of the system at 8-25°C, performing a polymerization reaction, and controlling the polymerization reaction time by the amount of initiator added. As the polymerization reaction proceeds, the system temperature slowly rises, and the highest temperature reaches 50-75°C.
[0020] The shell layer preparation polymerization process is as follows: monoacrylate and diacrylate of polyethylene glycol (PEG) are added to the polymerized emulsion. According to the principle of like-like-like-like, acrylate will penetrate the surfactant layer and enter between the water phase and the surfactant, wherein the PEG chain faces the water phase, and the acrylate chain is miscible with the surfactant, so that a shell layer composed of acrylate of polyethylene glycol (PEG) and surfactant is formed on the surface of the polymer particles. At this time, an initiator is added to initiate the polymerization of monoacrylate and diacrylate of polyethylene glycol (PEG), and the monoacrylate and diacrylate of polyethylene glycol (PEG) will be fixed on the polymer surface to form a shell layer. The specific process is that after the polymerization process is completed, the system temperature is maintained at 40-65° C., an appropriate amount of monoacrylate and diacrylate of polyethylene glycol (PEG) is added to the system, stirred for 10-60 minutes, and an appropriate amount of initiator is added to initiate the polymerization of the shell layer. The amount of the monoacrylate and diacrylate of polyethylene glycol (PEG) added is 0.5-2wt% of the total amount of the emulsion, wherein the mass ratio of the diacrylate of polyethylene glycol (PEG) to the monoacrylate of polyethylene glycol (PEG) is 3:1-5:1. The polymerization degree of PEG is 100, 200, 400 or 600. The initiator is an oil-soluble azo or peroxide, such as azobisisobutyronitrile, azobisisoheptylonitrile, and benzoyl peroxide.
[0021] The suspended particle separation and drying process includes: filtering the suspended particles in the above obtained suspension through a rotary vibrating screen, and the filtered particles enter the drying equipment for drying. The drying equipment is preferably a fluidized bed, and the temperature of each section is controlled so that the final product solid content is ≥88%. When the polymer particles are dispersed in water, the mechanism of action is the same as that of the emulsion product. The polymer protected by the shell layer only expands slightly. After a period of time, the acrylic acid ester of the shell layer is hydrolyzed, the shell layer is broken, and the polymer inside is slowly released, achieving the effect of viscosity slow release.
[0022] The beneficial effects of the present invention are as follows: the high temperature-resistant and salt-resistant oil-displacing polymer with viscosity slow-release performance of the present application is completed in two steps. The first step is to introduce a temperature-resistant and salt-resistant monomer into the molecular structure of polyacrylamide, so that the polymer has certain temperature-resistant and salt-resistant ability in structure, and at the same time, obtain ultra-high molecular weight linear products through emulsion or suspension polymerization; the second step is to coat the outer layer of the obtained ultra-high molecular weight polymer particles with a shell layer that dissolves slowly. When the polymer is dispersed in water, it is protected by the hydrophobicity of the shell layer, and the polymer in the shell layer is almost not in contact with water, so the polymer only expands slightly. After a period of time, the acrylic acid ester of the shell layer is hydrolyzed, and the outer shell layer will be slowly dissolved by water at high temperature and slowly release the ultra-high molecular weight polymer inside, so as to achieve the effect of viscosity slow release. Due to the protective effect of the shell layer, the service life of the polymer is extended. This structure can greatly avoid the shearing of the ultra-high molecular weight and high viscosity polymer solution when passing through the blasthole and the near-well area, reduce the viscosity loss in the initial injection period, and improve the viscosity stability and action time of the polymer. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with embodiments:
[0024] Example 1: Preparation of emulsion-type viscosity sustained-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide: 1000 kg of No. 3 white oil was added to a 3-square-meter polymerization kettle equipped with a stirring device, and then 150 kg of Span80 and 10kgTween60 are stirred and mixed evenly; 1000kg deionized water, 800kg acrylamide, 80kg acrylic acid, and 150kgAMPS are added to another 3-square liquid preparation kettle equipped with a stirring device, and sodium hydroxide is added to adjust the pH value of the system to 7.5±0.5, and the temperature is lowered to 15°C, and 50g of initiator ammonium persulfate and 15g of water-soluble azodiisobutylamidine hydrochloride are added; the prepared aqueous phase is introduced into the polymerization kettle containing the organic phase through a bottom pump, stirred and mixed, and further emulsified by an emulsification pump at the bottom of the kettle to obtain a more stable emulsion; nitrogen is introduced into the polymerization kettle, and the temperature is lowered to 10°C. After 30 minutes, 5g of sodium sulfite is weighed, dissolved in 2 liters of deionized water, and added into the polymerization kettle through the feeding port on the polymerization kettle to carry out polymerization reaction. Cooling liquid is introduced into the jacket and coil of the polymerization kettle to control the temperature so that the final temperature of the system is lower than 75°C. The final polymerization time is about 5 hours; when the polymerization temperature no longer rises, continue to keep warm for 1 hour, then cool to 60°C, add a mixture of 15kg of PEG-200 monoacrylate and 45kg of PEG-600 diacrylate into the polymerization kettle, stir for 1 hour, weigh 50g of azobisisobutyronitrile and dissolve it in 2 liters of xylene, add it into the polymerization kettle through the feeding port on the polymerization kettle, and polymerize the PEG acrylate to form a shell layer. After the polymerization is completed, the emulsion is cooled to below 30°C and transferred from the polymerization kettle to the reverse phase kettle, and 150kg of AEO-9 is added and stirred for 1 hour. A milky white low-viscosity emulsion is obtained, which is packed into ton barrels as a finished product.
[0025] The obtained product was dissolved in type II water (mineralization degree was 19334 mg / L), the emulsion concentration was 5000 ppm, and after dissolution, it was transferred to an ampoule, and the ampoule was sealed after nitrogen deoxygenation. The ampoule was placed in a 75°C oven, and the viscosity was measured at 75°C at regular intervals, and compared with the same emulsion without adding PEG acrylate, and the results are shown in Table 1. The viscosity value of the viscosity-slow-release high-temperature-resistant and salt-resistant oil-displacement polyacrylamide at 90 days was significantly higher than that of ordinary products.
[0026] Table 1 Comparison of temperature aging resistance of type II aqueous viscosity sustained-release polyacrylamide and common products
[0027] sample 0 day (mPa.s) 30 days (mPa.s) 60 days (mPa.s) 90 days (mPa.s) Viscosity sustained release samples 3 13.3 12.9 11.7 Ordinary samples 13.5 12.4 10.9 10.1
[0028] Example 2: Preparation of emulsion type viscosity sustained release high temperature resistance and salt resistance oil displacement polyacrylamide: 800 kg of No. 3 white oil was added to a 3-square polymerization kettle equipped with a stirring device, and then 120 kg of Span80 and 15kgTween20 are stirred and mixed evenly; 1100kg deionized water, 600kg acrylamide, 50kg acrylic acid, 400kgAMPS are added to another 3-square liquid preparation kettle equipped with a stirring device, and sodium hydroxide is added to adjust the pH value of the system to 7.5±0.5, and the temperature is lowered to 15°C, and 35g of initiator tert-butyl hydroperoxide and 20g of azobispropaneamine are added; the prepared aqueous phase is introduced into the polymerization kettle containing the organic phase through a bottom pump, and stirred and mixed, and further emulsified by an emulsification pump at the bottom of the kettle to obtain a more stable emulsion; nitrogen is introduced into the polymerization kettle, and the temperature is lowered to 10°C at the same time. After 30 minutes, 4g of sodium sulfite is weighed, dissolved in 2 liters of deionized water, and added into the polymerization kettle through the feeding port on the polymerization kettle to carry out polymerization reaction. Cooling liquid is introduced into the jacket and coil of the polymerization kettle to control the temperature so that the final temperature of the system is lower than 75°C. The final polymerization time is about 5 hours; when the polymerization temperature no longer rises, continue to keep warm for 1 hour, then cool to 60°C, add a mixture of 20kg of PEG-400 monoacrylate and 20kg of PEG-400 diacrylate into the polymerization kettle, stir for 1 hour, weigh 20g of benzoyl peroxide and dissolve it in 2 liters of xylene, add it into the polymerization kettle through the feeding port on the polymerization kettle, and polymerize the PEG acrylate to form a shell layer. After the polymerization is completed, the emulsion is cooled to below 30°C and transferred from the polymerization kettle to the reverse phase kettle, and 200kg of lauryl alcohol polyoxyethylene ether is added and stirred for 1 hour. A milky white low-viscosity emulsion is obtained, which is packed into ton barrels as a finished product.
[0029] The obtained product was dissolved in type III water (mineralization degree was 32868 mg / L), the emulsion concentration was 5000 ppm, and after dissolution, it was transferred to an ampoule, and the ampoule was sealed after nitrogen deoxygenation. The ampoule was placed in a 95°C oven, and the viscosity was measured at 95°C at regular intervals, and compared with the same emulsion without adding PEG acrylate, and the results are shown in Table 2. The viscosity value of the viscosity sustained-release high temperature-resistant and salt-resistant oil-displacement polyacrylamide at 90 days was significantly higher than that of ordinary products.
[0030] Table 2 Comparison of temperature aging resistance of three types of water viscosity sustained-release polyacrylamide and ordinary products
[0031] sample 0 day (mPa.s) 30 days (mPa.s) 60 days (mPa.s) 90 days (mPa.s) Viscosity sustained release samples 2.8 10.1 9.4 7.9 Ordinary samples 10.3 9.5 8 6.7
[0032] Example 3: Preparation of dry powder type viscosity sustained release high temperature resistance and salt resistance oil displacement polyacrylamide: 1500kg No. 3 white oil was added to a 3-square polymerization kettle equipped with a stirring device, and then 30kg Span80, stir and mix evenly; add 1200kg deionized water, 300kg acrylamide, 300kg dimethylacrylamide, 400kg AMPS into another 3-square liquid preparation kettle equipped with a stirring device, add sodium hydroxide to adjust the pH value of the system to 7.5±0.5, cool to 15°C, add 20g of initiator tert-butyl hydroperoxide and 20g of azobisisobutylamidine hydrochloride; introduce the prepared aqueous phase into the polymerization kettle containing the organic phase through a bottom pump and stir and mix, and the stirring speed is controlled at 150 rpm; nitrogen is introduced into the polymerization kettle, and the temperature is reduced to 10°C at the same time. After 30 minutes, 3g of ferrous sulfate heptahydrate is weighed, dissolved in 2 liters of deionized water, and added into the polymerization kettle through the feeding port on the polymerization kettle to carry out polymerization reaction. The jacket and coil of the polymerization kettle are passed through a cooling liquid to control the temperature so that the final temperature of the system is lower than 65°C. The final polymerization time is about 3 hours; when the polymerization temperature no longer rises, continue to keep warm for 1 hour, then cool to 60°C, add a mixture of 20kg of PEG-100 monoacrylate and 40kg of PEG-200 diacrylate into the polymerization kettle, stir for 1 hour, weigh 30g of benzoyl peroxide and dissolve it in 2 liters of xylene, add it into the polymerization kettle through the feeding port on the polymerization kettle, and polymerize the PEG acrylate to form a shell layer. After the polymerization is completed, transfer the suspension to the filtration equipment, select an 80-mesh filter, and convey the filtered particles to the fluidized bed dryer. The temperature of the first stage is controlled at 120°C, and the second stage is 80°C. The solid content of the dried powder particles is ≥88%, and they can be directly packed into ton bags without crushing to form finished products. The filtered filtrate can continue to be used for the organic phase of the synthetic reaction.
[0033] The obtained product was dissolved and dispersed in 1.5 times the concentration of type III water (mineralization degree is 49302mg / L), the polymer concentration is 2000ppm, and after dissolution, it was transferred to an ampoule, and the ampoule was sealed after nitrogen deoxygenation. The ampoule was placed in a 100℃ oven, and the viscosity was measured at 100℃ at regular intervals, and compared with the same dry powder but without adding PEG acrylate, the results are shown in Table 3. The viscosity value of the viscosity sustained-release high temperature and salt resistance oil displacement polyacrylamide in 90 days is significantly higher than that of ordinary products.
[0034] Table 3 Comparison of temperature aging resistance between 1.5 times the viscosity of Type III sustained-release polyacrylamide in water and ordinary products
[0035] sample 0 day (mPa.s) 30 days (mPa.s) 60 days (mPa.s) 90 days (mPa.s) Viscosity sustained release samples 3.2 11.3 10.7 9.2 Ordinary samples 11.2 10.6 9.3 8.4
[0036] Example 4: Preparation of dry powder type viscosity sustained release high temperature resistance and salt resistance oil displacement polyacrylamide: 2000 kg No. 3 white oil was added to a 3-square polymerization kettle equipped with a stirring device, and then 10 kg Span80, 15kg of ethyl cellulose were stirred and mixed evenly; 1000kg of deionized water, 50kg of acrylamide, 100kg of dimethylacrylamide, 100kg of tert-butylacrylamide, and 600kg of AMPS were added to another 3-square liquid preparation kettle equipped with a stirring device, and sodium hydroxide was added to adjust the pH value of the system to 7.5±0.5, and the temperature was lowered to 15°C, and 15g of initiator potassium persulfate and 10g of azobiscyanovaleric acid were added; the prepared aqueous phase was introduced into the polymerization kettle containing the organic phase through a bottom pump and stirred and mixed, and the stirring speed was controlled at 120 rpm; nitrogen was introduced into the polymerization kettle, and the temperature was lowered to 10°C at the same time. After 30 minutes, 2g of ferrous sulfate heptahydrate was weighed, dissolved in 2 liters of deionized water, and added into the polymerization kettle through the feeding port on the polymerization kettle to carry out polymerization reaction. The jacket and coil of the polymerization kettle were passed with cooling liquid to control the temperature so that the final temperature of the system was lower than 65°C. The final polymerization time is about 4 hours; when the polymerization temperature no longer rises, continue to keep warm for 1 hour, then cool to 45°C, add a mixture of 15kg of PEG-600 monoacrylate and 40kg of PEG-100 diacrylate into the polymerization kettle, stir for 1 hour, weigh 20g of benzoyl peroxide and dissolve it in 1 liter of xylene, add it into the polymerization kettle through the feeding port on the polymerization kettle, and polymerize the PEG acrylate to form a shell layer. After the polymerization is completed, transfer the suspension to the filtration equipment, select the particles filtered by the 80-mesh filter and transport them to the fluidized bed dryer. The temperature of the first stage is controlled at 120°C, and the second stage is 80°C. The solid content of the dried powder particles is ≥88%, and they can be directly packed into ton bags without crushing to form finished products.
[0037] The obtained product was dissolved and dispersed in 1.5 times the concentration of Type III water (mineralization degree is 49302mg / L), the polymer concentration is 2500ppm, and after dissolution, it was transferred to an autoclave, and the autoclave was sealed after nitrogen deoxygenation. The autoclave was placed in a 110℃ oven, and the viscosity was measured at 110℃ at regular intervals, and compared with the same dry powder but without adding PEG acrylate, the results are shown in Table 4. The viscosity value of the viscosity sustained-release high temperature and salt resistance oil displacement polyacrylamide in 90 days is significantly higher than that of ordinary products.
[0038] Table 4 Comparison of temperature aging resistance between 1.5 times the viscosity of Type III sustained-release polyacrylamide in water and ordinary products
[0039] sample 0 day (mPa.s) 30 days (mPa.s) 60 days (mPa.s) 90 days (mPa.s) Viscosity sustained release samples 3.6 11.5 10.8 9.5 Ordinary samples 11.7 10.5 9.4 8.1
Claims
1. A method for preparing a viscosity sustained-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide emulsion, wherein the polyacrylamide emulsion is obtained by water-in-oil, i.e., reverse emulsion polymerization, including a reverse emulsion polymerization process, a shell polymerization preparation process, and a phase inversion treatment process of the emulsion after polymerization; The reverse phase emulsion comprises 10-40wt% of an organic solvent, 0.5-20wt% of a surfactant added before polymerization, 0.5-10wt% of a surfactant for phase inversion, 5-50wt% of water, 10-45wt% of a monomer, a base to make the final pH of the system between 6-8, and an initiator in an amount of 0.001-1wt% of the total monomer amount; wherein the monomer comprises a nonionic monomer and an anionic monomer, the amount of the nonionic monomer accounts for 30-95wt% of the total monomer amount, and the anionic monomer accounts for 5-70wt% of the total monomer amount; wherein the initiator is a redox initiator or a mixture of a redox initiator and a water-soluble azo initiator in any mass ratio; the above amounts are calculated in mass percentage; The polymerization process of the inverse emulsion include: (1) Preparation of the organic phase: add an organic solvent to a polymerization kettle equipped with a stirring device, then continue to add a surfactant or a mixture of surfactants to the polymerization kettle, and stir and mix them evenly; (2) Preparation of the aqueous phase: add water to another liquid preparation kettle equipped with a stirring device, then add monomers in sequence, add alkali to adjust the pH value of the system, cool down, and add initiator; (3) Mixing and emulsification: introduce the prepared aqueous phase into the polymerization kettle containing the organic phase, stir and mix, and further emulsify it through an emulsification pump at the bottom of the kettle to obtain a more stable emulsion; (4) Polymerization: introduce an inert gas into the polymerization kettle, and at the same time control the starting temperature of the system at 8-25°C to carry out the polymerization reaction. The polymerization reaction time is controlled by the amount of initiator added. As the polymerization reaction proceeds, the system temperature gradually increases, and the maximum temperature reaches 50-75°C; The shell layer preparation polymerization process is as follows: adding monoacrylate and diacrylate of polyethylene glycol to the polymerized emulsion, according to the principle of like dissolves like, the monoacrylate and diacrylate of polyethylene glycol will penetrate the surfactant layer and enter between the water phase and the surfactant, wherein the polyethylene glycol PEG chain faces the water phase, and the acrylic acid chain is miscible with the surfactant, so that a shell layer composed of monoacrylate and diacrylate of polyethylene glycol and the surfactant is formed on the surface of the polymer particles, and then adding an initiator to initiate the polymerization of monoacrylate and diacrylate of polyethylene glycol, and the monoacrylate and diacrylate of polyethylene glycol will be fixed on the surface of the polymer to form a shell layer; the specific process is as follows: after the polymerization process is completed, the system temperature is maintained at 40-65°C, an appropriate amount of monoacrylate and diacrylate of polyethylene glycol is added to the system, and the mixture is stirred for 10-60 minutes; min, adding a proper amount of initiator to initiate shell polymerization, wherein the amount of the monoacrylate and diacrylate of polyethylene glycol added is 0.5-2wt% of the total amount of the emulsion, wherein the mass ratio of the diacrylate of polyethylene glycol to the monoacrylate of polyethylene glycol is 3:1-5:1, the degree of polymerization of PEG is 100, 200, 400 or 600, and the initiator is an oil-soluble azo or peroxide; The nonionic monomer is one of acrylamide, 2-methylacrylamide, N-tert-butylacrylamide, N,N-dimethylacrylamide, or a mixture of two of them in any mass ratio; the anionic monomer is one of acrylic acid, methacrylic acid, itaconic acid, maleic acid, 2-acrylamido-2-methylpropanesulfonic acid, methylallylsulfonic acid, and vinylbenzenesulfonic acid, or a mixture of two of them in any mass ratio.
2. A method for preparing a viscosity sustained-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide emulsion according to claim 1, Features: The phase inversion process is as follows: after the shell layer preparation polymerization reaction is completed, the system is cooled to below 30°C, the required surfactant for phase inversion is added to the polymerization kettle, stirred for 30-60 minutes, the emulsion is subjected to phase inversion treatment, and the finished product is obtained after the phase inversion.
3. A method for preparing a viscosity sustained-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide emulsion according to claim 2, Features: The organic solvent is one of toluene, xylene, normal alkane, isoalkane, petroleum ether, liquid paraffin, kerosene and diesel, or a mixture of two or more of them in any mass ratio; the surfactant added before polymerization is one of glyceryl monostearate, sorbitan monooleate, sorbitan monostearate, sorbitan monopalmitate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether and polyoxyethylene sorbitan monostearate, or a mixture of two of them in any mass ratio; the surfactant having a phase inversion effect is one of nonionic surfactant or anionic surfactant, or a mixture of two of them in any mass ratio; the nonionic surfactant is fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, alkylphenol polyoxyethylene ether, The invention discloses a kind of redox initiator, which is one of the group consisting of vinyl ether, fatty amine polyoxyethylene ether, and alkyl alcohol amide polyoxyethylene ether; the anionic surfactant is one of the group consisting of sodium dodecylbenzene sulfonate and sodium sulfate of fatty alcohol polyoxyethylene ether; the water is deionized water or distilled water; the alkali is one of the group consisting of sodium hydroxide, potassium hydroxide, sodium carbonate, and ammonia water; the oxidant in the redox initiator is ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, or isopropylbenzene hydroperoxide; the reducing agent in the redox initiator is sodium sulfite, sodium bisulfite, sodium pyrosulfite, ferrous sulfate, tetramethylethylenediamine, or β-dimethylaminopropionitrile; and the water-soluble azo is azobisisobutylamine hydrochloride, azobispropaneamine, or azobiscyanovaleric acid.
4. A method for preparing viscosity slow-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide particles, the method is to obtain acrylamide particles by suspension polymerization, including a polymerization process of suspension polymerization, a preparation polymerization of the shell layer and a separation and drying process of the suspended particles; The suspension of the suspension polymerization comprises an organic solvent in an amount of 40-80wt%, a suspending agent in an amount of 0.1-2wt%, water, a monomer in an amount of 10-45wt%, a base so that the final pH of the system is between 6-8, and an initiator in an amount of 0.001-1wt% of the total amount of the monomer, wherein the amount of water accounts for 50-80wt% of the total amount of water and the monomer; the monomer comprises a nonionic monomer and an anionic monomer, wherein the amount of the nonionic monomer accounts for 30-95wt% of the total amount of the monomer, and the amount of the anionic monomer accounts for 5-70wt% of the total amount of the monomer; the initiator is a redox initiator or a composite initiator of a redox initiator and a water-soluble azo initiator; the above amounts are calculated by mass percentage; The polymerization process of suspension polymerization include: (1) Preparation of the organic phase: Add an organic solvent to a polymerization kettle equipped with a stirring device, then continue to add a suspending agent to the polymerization kettle and stir to mix evenly; (2) Preparation of the aqueous phase: Add water to another liquid preparation kettle equipped with a stirring device, then add the monomers in order, add alkali to adjust the pH value of the system, cool down, and add the initiator; (3) Mix and stir: introduce the prepared aqueous phase into the polymerization kettle containing the organic phase and stir and mix. Control the stirring speed so that the size of the suspended particles is 0.5-2mm; (4) Polymerization: Introduce an inert gas into the polymerization kettle, and control the starting temperature of the system at 8-25°C to carry out the polymerization reaction. The polymerization reaction time is controlled by the amount of initiator added. As the polymerization reaction proceeds, the system temperature gradually rises, and the maximum temperature reaches 50-75°C; The shell layer preparation polymerization process is as follows: monoacrylate and diacrylate of polyethylene glycol PEG are added to the polymerized emulsion. According to the principle of like-like-like-like, monoacrylate and diacrylate of polyethylene glycol PEG will penetrate the surfactant layer and enter between the aqueous phase and the surfactant, wherein the PEG chain faces the aqueous phase, and the acrylic acid chain is miscible with the surfactant, so that a shell layer composed of polyethylene glycol acrylate and surfactant is formed on the surface of the polymer particles. At this time, an initiator is added to initiate the polymerization of monoacrylate and diacrylate of polyethylene glycol PEG, and the monoacrylate and diacrylate of polyethylene glycol PEG will be fixed on the polymer surface to form a shell layer. The specific process is as follows: after the polymerization process is completed, the system temperature is maintained at 40-65°C, an appropriate amount of monoacrylate and diacrylate of polyethylene glycol PEG is added to the system, and the mixture is stirred for 10-60 minutes. min, adding an appropriate amount of initiator to initiate shell polymerization, wherein the amount of the monoacrylate and diacrylate of polyethylene glycol PEG added accounts for 0.5-2wt% of the total amount of the emulsion, wherein the mass ratio of the diacrylate of polyethylene glycol PEG to the monoacrylate of polyethylene glycol PEG is 3:1-5:1, and the degree of polymerization of PEG is 100, 200, 400, 600; The nonionic monomer is one of acrylamide, 2-methylacrylamide, N-tert-butylacrylamide, N,N-dimethylacrylamide, or a mixture of two of them in any mass ratio; the anionic monomer is one of acrylic acid, methacrylic acid, itaconic acid, maleic acid, 2-acrylamido-2-methylpropanesulfonic acid, methylallylsulfonic acid, and vinylbenzenesulfonic acid, or a mixture of two of them in any mass ratio.
5. According to the method for preparing a viscosity sustained-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide particles as described in claim 4, Features: The suspended particle separation and drying process includes: filtering the suspended particles in the obtained polymerization system through a rotary vibrating screen, and the filtered particles enter the drying equipment for drying. The drying equipment is a fluidized bed, and the temperature of each section is controlled so that the final product solid content is ≥88%. When the polymer particles are dispersed in water, the mechanism of action is the same as that of the emulsion product. The polymer protected by the shell layer only expands slightly. After a period of time, the acrylic ester of the shell layer is hydrolyzed, the shell layer ruptures, and the polymer inside is slowly released, achieving the effect of viscosity sustained release.
6. According to the method for preparing a viscosity sustained-release high-temperature-resistant and salt-resistant oil-displacing polyacrylamide particles as described in claim 5, Features: The organic solvent is one of toluene, xylene, normal alkane, isoalkane, petroleum ether, liquid paraffin, kerosene, and diesel, or a mixture of two of them in any mass ratio; the suspending agent is a surfactant or a polymer, the suspending agent of the surfactant type is one of sorbitan monopalmitate, sorbitan monostearate, sorbitan tristearate, and sorbitan monooleate, the polymer suspending agent is one of polydodecyl methacrylate and ethyl cellulose, the water is deionized water or distilled water; the alkali is one of sodium hydroxide, potassium hydroxide, and sodium carbonate, and the induction The initiator is a redox initiator or a composite initiator of a redox initiator and a water-soluble azo initiator in any mass ratio. The oxidant in the redox initiator is ammonium persulfate, sodium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl hydroperoxide or isopropylbenzene hydroperoxide; the reducing agent in the redox initiator is one of sodium sulfite, sodium bisulfite, sodium pyrosulfite, ferrous sulfate, tetramethylethylenediamine, and β-dimethylaminopropionitrile; the water-soluble azo initiator is one of azobisisobutylamine hydrochloride, azobispropaneamine, and azobiscyanovaleric acid.
Citation Information
Patent Citations
Polymer microsphere for oil field profile control and water plugging and preparation method thereof
CN105778016A
Core-shell type polymer microsphere and preparation method thereof
CN109666099A
Multilayer core-shell structure polymer microsphere, modifying and flooding agent, and preparation method and application thereof
CN111087553A
Slow-release tackifying polymer microsphere and preparation method thereof
CN116284561A
Method for preparation of phase reversing core / shell type microgel
KR1020000046306A
